a) 3 * x + 5= 38
b) 7*x-10= -24
a) 5*x-7-x=9-2*x-4
b) 1-2*x-12-7*x=3*x+10-5*x



Odpowiedź :

Odpowiedź:

a) 3 · x + 5= 38

3x = 33

x=11

b) 7·x-10= -24

7x = -14

x = -2

a) 5·x-7-x=9-2·x-4

5x-x+2x=7 +9 -4

6x = 12

x=2

b) 1-2·x-12-7·x=3·x+10-5·x

-2x -7x -3x +5x= 10 -1 +12

-7x = 21

x = -3

Szczegółowe wyjaśnienie:

Odpowiedź:

a) 3 * x + 5 = 38

3 x + 5 = 38    | -5

3x = 33      | :3

x = 11

b) 7 * x - 10= -24

7x - 10 = -24    | +10

7x = -14  | :7

x = -2

c) 5 * x - 7 - x = 9 - 2 * x - 4

5x - 7 - x = 9 - 2x - 4

4x - 7 = 5 - 2x    | +2x

6x - 7 = 5    | +7

6x = 12   | :6

x = 2

d) 1 - 2 * x - 12 - 7 * x = 3 * x + 10 - 5 * x

1 - 2x - 12 - 7x = 3x + 10 - 5x

-11 - 5x = - 2x + 10     | +2x

-11 - 3x = 10   | +11

- 3x = 21   | (-3)

x = -7